Solenanthus strictissimus (Boraginaceae)—an overlooked mountain species from Central Asia - Sutorý, Karel (Phytotaxa, 2017)
The Central Asian mountain species Solenanthus strictissimus has not been distinguished from similar species such as Solenanthus stamineus or less often from Solenanthus kokanicus. Its narrow leaves and particularly the character of its nutlets are sufficient to separate it from the others. To date, its distribution is known to be restricted to two localities in Afghanistan. In this contribution it is extended to the mountains running from West Pakistan and east Tajikistan in the east, through north, east and central Afghanistan into east Iran. A Lectotype was selected among four known syntypes.